Branding an employer as attractive to Finnish and international business students - Aarnio, Nelli; Halmetoja, Terhi (2025)
The internationalization of Finland’s labor market, especially the capital region, creates both opportunities and new challenges for employers in managing international talent and navigating culturally diverse communication practices. Employer branding is a widely used activity in organizations for enhancing employer image and attractiveness. This thesis aims to provide a preliminary understanding of how organizations in Finland can tailor their employer branding strategies to appeal to a diverse and talented workforce, ensuring competitiveness and success in an evolving, globalizing labor market. This research was conducted as 4 focus groups: 2 for Finnish students, 2 for international students. The participants were Finnish and international students studying business in their final years of study at the University of Jyväskylä in Finland. Each group size is 4-6 participants. The focus groups were asked to discuss what items of Berthon et al. (2005) Employer Attractiveness Scale they find more or less important when considering their employer of choice. The results of this study provide valuable insights into the variance and importance of tailoring employer branding strategies to meet the diverse expectations of both local and international business students providing more evidence to the findings from previous international studies. The findings highlight that while certain values, such as social relationships and development opportunities, are appreciated universally, there are clear distinctions in what different groups perceive as attractive in an employer. The results differed significantly between Finnish and international students. These insights underscore a crucial need for companies operating in Finland, or aiming to attract international talent, to refine their employer branding with intercultural awareness.